Our Mythical Education The Reception of Classical Myth Worldwide in Formal Education, 1900-2020 - Maurice, Lisa (University of Warsaw Press, 2020)
Clearly, wherever myth forms part of an educational syllabus, value judgements have been made by those who chose the texts, with regard to content, approach, usage, emphases, purpose and many other elements. [...] the present volume examines the reception of such myth within formal education in the twentieth and twenty-first centuries [...]. It focuses for the most part on school education, but with forays into post-high school where relevant, and includes a wide geographical and chronological range. With regard to the latter limitations, the general emphasis is on modern day, and the current situation, but as a result of individual historical circumstances in each example. Lisa Maurice, Editor of the Volume This is a task of paramount importance, as educational processes have a lasting influence on us - all the more so as we are exposed to them already in childhood, when the capacity for critical thinking is being formed by none other than school curricula shaped and developed in specific circumstances. This volume makes us aware of these complex processes, their implications, and the opportunities they create for the future of Classical Antiquity. Katarzyna Marciniak, Editor of the Series